Innovative Work Behaviour in Local Government: Innovation Process and Gender Differences - Pradana, I Putu Yoga Bumi; Sayrani, Laurensius Petrus; Pah, Theny Intan Berlian Kurniati; Wijayanti, Nadia Sasmita; Saputra, Boni; Rijoly, Jacobus Cliff Diky (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2025)
This research aims to identify and understand the barriers affecting public sector employees' innovative behaviors, particularly examining how these obstacles differ across stages of innovation and between genders. Utilizing a qualitative phenomenological approach, the research involved in-depth interviews with 40 informants from six agencies in Kupang City and Kupang Regency. Data were analyzed through thematic analysis techniques, revealing eleven major barriers categorized into political-administrative leadership, public management, and individual factors. Political-administrative barriers include insufficient support from political actors and a restrictive organizational climate. Public management challenges encompass a risk-averse culture, weak interdepartmental collaboration, limited knowledge sharing, bureaucratic constraints, and regulatory rigidity that restricts creative ideas perceived as "out of the box." Another key finding highlights the demotivating effect of redundant local digital innovations replaced by centrally mandated platforms, fostering employee frustration and discouragement. Individual barriers identified include a lack of expertise, limited access to policymakers, and significant gender-related issues such as patriarchy, stereotypes, and domestic responsibilities. The study highlights its novelty by uncovering how regional contextual factors, especially gender dynamics, uniquely shape barriers to innovation. This study uniquely contributes to the literature by specifically examining barriers to innovative work behavior (IWB) in the under-researched context of Eastern Indonesia, focusing on both innovation stages and gender differences.